Analysis of Cumulative Energy Demand Potential Using Life Cycle Assessment Approach: A Case Study of XYZ Laboratory - Samadikun, Budi Prasetyo; Syafrudin, Syafrudin; Wahyuni, Retno Hari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Environmental issues such as ecosystem damage, degradation and climate change require effective environmental management strategy. This study analyzes the cumulative energy demand (CED) potential of the XYZ Laboratory activities using a Life Cycle Assessment (LCA) approach. The LCA methodology, adhering to ISO 14040 and ISO 14044 standards, encompasses goal and scope definition, inventory analysis, impact assesment, and interpretation. Data were collected from XYZ Laboratory's activities during 2023, focusing on four main process units: sample administration, fulfillment of testing laboratory conditions, sample preparation, and instrumentation analysis. The environmental impact of CED was characterized using OpenLCA version 2.0 software with the Ecoinvent database and then calculated using a spreadsheet. The result is XYZ Laboratory have a significant environmental impact. The instrumentation analysis stage and sample preparation stage are the two highest potential impacts of CED with a contribution of 52.559 MJ per analysis service (50.948%) and 35.970 MJ per analysis service (34.867%).The study concludes that significant efforts are required to reduce energy use and environmental impact, suggesting techniques such as good housekeeping, input change, better process control, technology change, on-site reuse and recycling, and production of useful by-products. These strategies aim to enhance energy efficiency of laboratory operations.